Differences Between Pediatric and Adult T Cell Responses to In Vitro Staphylococcal Enterotoxin B Stimulation - Rudolph, Mark E.; McArthur, Monica A.; Barnes, Robin S.; Magder, Laurence S.; Chen, Wilbur H.; Sztein, Marcelo B. (Frontiers in Immunology, 2018)
Toxic shock syndrome (TSS) is capable of inducing life-threatening fever, rash, and systemic organ failure, though the specific mechanisms behind these symptoms remain poorly understood. Staphylococcal enterotoxin B (SEB) and other superantigens have shown to be important factors in TSS, capable of promoting cross-linking between T cell receptors (TCR) and major histocompatibility complexes (MHC) which results in overwhelming T cell activation, proliferation, and cytokine production. The resulting pro-inflammatory cytokine cascade, often referred to as the “cytokine storm”, seems to be critical to the development of disease. Interestingly, clinical studies have shown that children exhibit less severe TSS-associated morbidity than adults, though the mechanism behind this phenomenon has not been addressed. Indeed, despite the fact that most novel antigen exposure occurs early in life, be it from environmentally acquired pathogens or routine vaccination, normal pediatric T cell immune functions remain critically underexplored. This is largely due to difficulty in obtaining enough samples to explore more than a narrow sliver of the cell mediated immune (CMI) compartment. To address this limitation, we optimized a T effector (Teff) / circulating T follicular helper (cTFH) cell mass cytometry panel which allowed us to analyze a wide array of T cell populations and effector functions following in vitro SEB stimulation. We show that T cell activation-- as measured by CD69 expression-- following SEB stimulation is lower in pediatric participants, increasing throughout childhood, and reaching adult levels by around 15 years-old. Further, while individual CD4+ effector memory T cell (TEM) effector molecules show limited age-associated differences following SEB stimulation, multifunctional CD4+ TEM are shown to positively correlate with increasing age through adolescence. Individual CD8+ TEM effectors and multifunctional phenotypes also show very strong age-associated increases following SEB stimulation. SEB stimulation has little impact on cTFH activation or functional cellular markers, regardless of age. These results, coupled with the fact that a robust pro-inflammatory cytokine response seems critical to developing severe TSS, suggest a possible connection between the significantly reduced T cell activation and multifunctional populations following in vitro SEB stimulation in our pediatric participants and clinical observations relating to reduced TSS mortality in children.